Evaluating the Outstanding Performance of Directors of Departments in the Ministry of Youth and Sports from the Perspective of Their Employees (Damu Journal of Sport Sciences, 2025)
The current research aims to identify the reality of the outstanding performance of directors of departments in the Iraqi Ministry of Youth and Sports from the perspective of their employees. The human resource field consisted of employees in the departments of the Iraqi Ministry of Youth and Sports. The research was applied to departments in the Iraqi Ministry of Youth and Sports. The researcher identified his research community through a comprehensive census of all employees in the departments, totaling (496), distributed across (10) departments of the Iraqi Ministry of Youth and Sports, representing a percentage of (50%) of the original research community. The research sample consisted of (248) employees. The researcher recommended that managers of the Iraqi Ministry of Youth and Sports encourage employees to think creatively (outside the box) in order to perform their work properly. The directors of the Iraqi Ministry of Youth and Sports must be highly competent to serve as good role models for their employees. Highly precise controls and standards must be applied when hiring employees, based on qualifications, academic achievement, and the extent of their soft skills in dealing with others.